Co-use of cigarettes and cannabis among people with HIV: Results from a randomized controlled smoking cessation trial - Jenny E. Ozga; Jonathan Shuter; Geetanjali Chander; Amanda L. Graham; Ryung S. Kim; Cassandra A. Stanton (Drug and Alcohol Dependence Reports, 2023)
Significance: People with HIV (PWH) who smoke cigarettes have lower cessation rates than the general population. This study investigated whether changes in cannabis use frequency impedes cigarette cessation among PWH who are motivated to quit. Methods: Between 2016-2020, PWH who smoked cigarettes were enrolled in a randomized controlled trial for cigarette cessation. Analyses were limited to PWH who reported on their past 30-day (P30D) cannabis use during four study visits (baseline, 1-month, 3-month, and 6-month) (N=374). Descriptive statistics and multivariable logistic regression were used to evaluate changes in cannabis use frequency from baseline to 6 months and associations with cigarette abstinence at 6 months among PWH who reported no use during all four visits (n=176), as well as those who reported use during at least one visit and who increased (n=39), decreased (n=78), or had no change (n=81) in use frequency. Results: Among those who reported cannabis use during at least one visit (n=198), at baseline, 18.2% reported no use. At 6 months, 34.3% reported no use. Controlling for covariates, increased cannabis use frequency from baseline was associated with reduced odds of cigarette abstinence at 6 months versus decreased use frequency (aOR=0.22, 95% CI=0.03, 0.90) or no use at either time-point (aOR=0.25, 95% CI=0.04, 0.93). Conclusions: Increased cannabis use over 6 months was associated with reduced odds of cigarette smoking abstinence among PWH who were motivated to quit. Additional factors that influence cannabis use and cigarette cessation simultaneously are in need of further study.